A study on the efficiency of digital photography in advertising media / Muhammad Ammar Asyhraf Zainal Abidin - Zainal Abidin, Muhammad Ammar Asyhraf (2015)
A camera's shutter speed can control exposure, but it's also one of the most powerful creative tools in photography. It can convey motion, freeze action, and isolate subjects and smooth water, amongst other abilities. This tutorial describes how to achieve these various effects, in addition to hopefully stimulating other creative ideas for using shutter speed in everyday shots. For a background on how it factors into exposure, also see camera exposure, aperture, ISO and shutter speed. For a given exposure, SLR cameras also typically have a much greater range of selectable shutter speeds than compact cameras. For example, this range is roughly 13-14 stops (or 10,000X) with most SLR cameras, but often just 8-9 stops (or 500X) with compact cameras. See the tutorial on compact for more on this topic. While some might see still photography as restricting, many instead see this as liberating, because still capture enables nearly full control over how motion is conveyed.